In Search of the First Stars: An Ultra-compact and Very-low-metallicity Lyα Emitter Deep within the Epoch of Reionization - Willott, Chris J.; Asada, Yoshihisa; Iyer, Kartheik G.; Judež, Jon; Rihtaršič, Gregor; Martis, Nicholas S.; Sarrouh, Ghassan T. E.; Desprez, Guillaume; Harshan, Anishya; Mowla, Lamiya; Noirot, Gaël; Felicioni, Giordano; et al. (The Astrophysical journal, 2025)
We present JWST observations of a gravitationally lensed, extremely metal-poor galaxy at redshift z = 8.203 ± 0.001 from the CANUCS survey. Based on the low oxygen to Balmer line ratios, we infer a gas-phase metallicity of 12 + log(O/H) = 6.85 (1.4% solar), making CANUCS-A370-z8-LAE one of the most metal-poor galaxies known at z > 7. The galaxy has a high H β equivalent width of 225 ± 50 Å, small half-light radius of only r hl = 3 8 − 19 + 3 pc, and high star formation rate density of 50–100 M ⊙ yr −1 kpc −2 . The galaxy shows high-equivalent-width Ly α emission with an inferred Ly α escape fraction of 0.21 ± 0.05. The high escape fraction of Ly α is likely due to the compact starbursting nature of the galaxy combined with its location in an overdensity traced by at least two other galaxies spectroscopically confirmed to lie within δz = 0.01 that have helped to reionize the environment. The low metallicity of CANUCS-A370-z8-LAE is best explained by a model where infalling metal-poor gas dilutes the interstellar medium, rather than being a young galaxy forming its first stellar populations.